FERMENTATION QUALITY AND IN VITRO DIGESTIBILITY OF TOTAL MIXED RATION ENSILED WITH FRESH OLIVE CAKE - Murat Er; Umair Ahsan; Eren Kuter; Hulisi Akçay; Muhammad Shazaib Ramay; Derya Merve Karagöz; Mehmet Onur Takka (Journal of Animal and Plant Sciences, 2025)
This study aimed to investigate the fermentation characteristics, aerobic stability, and in vitro digestibility of the total mixed rations (TMR) ensiled with different amounts of fresh olive cake (OC). Three TMRs were ensiled with different OC percentages on DM basis; 0% OC (control); 10% OC (OC10), and 20% OC (OC20). For each group, 27 vacuum bags (silos; 81 bags in total) were prepared. Three bags from each group were opened on d 2, 4, 7, and 14 of ensiling to measure pH, and on d 21 and d 42 to evaluate the pH and aerobic stability. The remaining bags (9 from each group, 27 in total) were opened on d 60 to measure aerobic stability, fermentation quality (pH, organic acids, and NH3-N), nutritional compositions, and vitro digestibility. Increasing the OC inclusion in the TMRs increased the ether extract, neutral detergent fiber (NDF), acid detergent fiber (ADF), and acid detergent lignin (ADL) concentrations whereas, non-fibrous carbohydrates, water soluble carbohydrates, and total phenolic content decreased (P ≤ 0.05). The control group had lower pH compared to other groups during the fermentation period (P≤0.05). No significant differences were seen among the treatments for lactic acid and acetic acid concentrations. However, propionic acid was greater in OC10 group compared to control (P≤0.05). Dry matter (DM) loss and aerobic stability were not different among the groups. Flieg score was greater in control group in comparison with that of OC20 group (P =0.016). Relative feed value (RFV) was greater in OC20 group than other groups (P ≤ 0.001) whereas, control group had lower RFV than OC10 group (P ≤ 0.001). In vitro digestibility parameters were lower in OC20 group in comparison with other groups (P≤0.001). Consequently, the results demonstrated that ensiling of TMR with OC had a good quality fermentation profile and feed value. However, in vitro nutrient digestibility was dramatically reduced when OC was used at 20% in TMR on a DM basis. Therefore, the inclusion of OC up to 10% in ruminant diets seems liable.
Keywords: Ensiled total mixed ration; olive cake; in vitro digestibility; fermentations characteristics